The Implications of Aging on the Health Systems of the Pacific Islands: Challenges and Opportunities - Ian Anderson; Wayne Irava (Taylor & Francis Group, 2017)
Population aging presents substantial and unique challenges and opportunities to Pacific Island countries. The countries in this region currently have young populations, but the population is rapidly changing. With some of the highest rates of obesity and diabetes in the world, an aging population will-unless urgent action is taken-put additional pressure on all aspects of the health system: leadership and governance; health financing; health workforce, service delivery; drugs and equipment; and information systems. Pacific Island economies face a particular challenge in terms of health financing: government already finances and provides the majority of health services, but most countries have limited fiscal space to expand and deepen health services for growing and aging populations. Most countries cannot rely on a demographic dividend to finance and strengthen their health systems. Increased efficiency, particularly through better targeted primary and secondary prevention of noncommunicable diseases, is a particularly strategic and feasible investment in the Pacific, improving the health and well-being of those who will age and strengthening the effectiveness, efficiency, and affordability of the broader health system.